Pre-Service Teachers’ Awareness and Attitude Towards the Use of Open Educational Resources for Learning in Kano State, Nigeria - Abdu Danyaro; Ayodeji Gboyega Aladesusi; Adesoye Oladunni Ajamu; Adenike Foluke Adegbite; Justina Ojoma Attah (Suluh: Jurnal Bimbingan dan Konseling, 2024)
This study focused on the pre-service teachers’ awareness and attitude towards the use of Open Educational Resources for learning in Kano State, Nigeria. The research adopted a descriptive research design. A total of 315 pre-service teachers from two colleges of education out of four colleges in the state were purposively selected and these colleges of education are Federal College of Education, Kano and Sa’adatu Rimi College of Education, Kumbotso. The reliability results were 0.77 for Awareness and 0.79 for Attitude, Mean and simple percentages were used to analyse the research questions, while the hypotheses were tested using a t-test at 0.05 significant level. The findings revealed among others those pre-service teachers had a good awareness of the existence of OER and their attitude towards the use of OER for learning was positive. Also, there was no significant difference between the male and female pre-service teachers in their awareness and attitude towards the use of OER for learning in the sampled colleges of education-based gender. The study concluded among others that the awareness and positive attitude of pre-service teachers could affect the use of OER. The study recommended among others that federal, and State governments and colleges’ management should encourage pre-service teachers to adopt OER more in their learning and other academic activities.